IMPLEMENTASI KEBIJAKAN PEMERINTAH DALAM PENYELENGGARAAN PENDIDIKAN ANAK USIA DINI (PAUD) - Hasyim, Abd. Wahid; Suharyat, Yayat; ., Noerhidayah (Program Studi Magister Pendidikan Islam Universitas Islam 45, 2009)
This research has purpose to know how the implementation of government regulation in early age children education (PAUD) in Desa Sumber Jaya, Kecamatan Tambun Selatan, Kabupaten Bekasi.The results of the research indicated that government policy, especially in implementation of government regulation of No. 19 th. 2005 about teacher standart qualification for early age children education (PAUD) is still very low.